Computed Tomography Angiography findings can predict massive bleeding in head and neck tumours. Issue 125 (April 2020) - Cannavale, Alessandro; Corona, Mario; Nardis, Piergiorgio; De Rubeis, Gianluca; Cannavale, Giuseppe; Santoni, Mariangela; De Gyurgyokai, Simone Zilahi; Catalano, Carlo; Bezzi, Mario
Highlights: Triple phase CT angiography is essential to define head and neck tumour staging and vascular bundle involvement. Artery involvement and high T stage on routine CT angiography can predict massive bleeding in head and neck cancer. Specific head and neck arteries may be involved by a certain tumour and should be checked by the reporting radiologist Patients at higher risk of CBS may benefit from an early endovascular approach and/or surgery. Abstract: Purpose: The aim of our study was to assess CT angiography findings of head and neck tumours in predicting carotid blow out syndrome (CBS). Method: We retrospectively reviewed the records of patients with head and neck cancer who underwent invasive angiography for CBS at our Institution from July 2013–2019. All routine CT angiography scans were assessed for the following findings with a univariate logistic regression analysis: 1) 360 ° involvement of the suspect artery by the tumour; 2) tissue or tumour necrosis, which was defined as an hypodense area with lack of contrast enhancement in the soft tissues of the neck or tumour mass, adjacent to the suspected vessel; 3) calibre reduction of the culprit artery; 5) jugular vein infiltration. T stage was also included in the analysis. Results: A total of 24 patients who underwent routine CT angiogram neck and embolization for CBS were included in this study. Univariate logistic regression showed as 360 ° involvement of target vessel may significantly increase the risk of bleeding (OR 11.6, CI: 1.4–91.5; p = 0.01), along with T stage (OR 14.0, p = 0.03). Tumour necrosis and calibre vessel reduction were quite influential, but not significantly (i.e. tumour necrosis OR 5.0 95 % CI: 0.8–31.0, p = 0.08). Contingency table analysis found 360 ° vessel involvement with the highest sensitivity and PPV in predicting bleeding (87.5 % and 82.35 %, respectively). Conclusions: CT angiography imaging findings have the potential to identify patients with head and neck cancer at higher risk of bleeding.